Reflections on the patient-surgeon relationship at the beginning of the new millennium - Campos Pierri, Néstor (Cirugía del Uruguay, 2002)
First of all I want to thank the President of the Congress, my friend, Dr. Francisco Di Leoni for ask me to refer to an update issue about the Surgeon's relationship with his sick, but it is also an element of aging when one ponders about things that have evolved and that can serve for young surgeons, from colleagues who they have toiled for years with this beautiful profession.